Exposure to electromagnetic fields from smart utility meters in GB; part I) laboratory measurements. Issue 4 (21st March 2017) - Peyman, Azadeh; Addison, Darren; Mee, Terry; Goiceanu, Cristian; Maslanyj, Myron; Mann, Simon
Abstract : Laboratory measurements of electric fields have been carried out around examples of smart meter devices used in Great Britain. The aim was to quantify exposure of people to radiofrequency signals emitted from smart meter devices operating at 2.4 GHz, and then to compare this with international (ICNIRP) health‐related guidelines and with exposures from other telecommunication sources such as mobile phones and Wi‐Fi devices. The angular distribution of the electric fields from a sample of 39 smart meter devices was measured in a controlled laboratory environment. The angular direction where the power density was greatest was identified and the equivalent isotropically radiated power was determined in the same direction. Finally, measurements were carried out as a function of distance at the angles where maximum field strengths were recorded around each device. The maximum equivalent power density measured during transmission around smart meter devices at 0.5 m and beyond was 15 mWm −2, with an estimation of maximum duty factor of only 1%. One outlier device had a maximum power density of 91 mWm −2 . All power density measurements reported in this study were well below the 10 W m −2 ICNIRP reference level for the general public. Bioelectromagnetics. 2017;38:280–294. © 2017 Crown copyright. Bioelectromagnetics Published by Wiley Periodicals LLC on behalf of Bioelectromagnetics Society. This article is published with the permission of the Controller of HMSO and the Queen's Printer for Scotland.